PENINGKATAN KONSENTRASI SISWA DALAM MENGIKUTI SEMINAR DENGAN METODE DEMONSTRASI - Putri O. Hutasoit; Benida D. Nababan; Masri Sagala; Mawartini Siallagan; Damayanti Nababan (Universitas 17 Agustus 1945 Semarang, 2022)
Abstract The purpose of carrying out this activity is to increase the awareness of students of SMK N 1 Siatas Barita about the influence of promiscuity for the future. This research was conducted by making observations first then the observation data were collected to carry out seminar planning, then the educational seminar actions. The subject of this seminar is students of SMK Negeri 1 Siatas Barita. This activity is carried out in a day with 3 seminar sessions. Based on the Christian religious education seminar held at SMK Negeri 1 Siatas Barita, the application of the method is indeed able to increase student concentration by capturing the attention of students and thus students are able to see and analyze events that occur, even students are able to create ideas. Regarding the material for the